The Dynamics of Women's Involvement in the Formulation of Islamic Family Law in Indonesia: Analysis of Law No. 1 of 1974 - Adila, Queen; Ahmad, Zamzami (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
This study aims to uncover the history of family law formation in Indonesia, the role of women's groups in the legislative process, and women's efforts to support family law reform based on equality and justice. The research method used is normative legal research or library research, which involves analyzing bibliographic sources or secondary data. The findings of this study indicate that, first, Dutch colonialism influenced marriage law in Indonesia. Second, women had no role in the process of drafting family law, making them a minority and often placing them in stereotypical positions. Third, the standardization of roles in several articles of Law No. 1 of 1974 on Marriage and the Compilation of Islamic Law has driven women to fight for equality through family law reform. [Penelitian ini bertujuan untuk mengungkap sejarah pembentukan hukum keluarga di Indonesia, dan peran kelompok perempuan dalam proses legislasi, serta upaya perempuan dalam mendukung reformasi hukum keluarga yang berbasis kesetaraan dan keadilan. Metode penelitian yang digunakan yaitu, penelitian hukum normatif atau penelitian hukum kepustakaan, yang dilakukan dengan cara menganalisis bahan pustaka atau data sekunder. Hasil penelitian ini menunjukkan bahwa pertama, kolonialisme Belanda berpengaruh terhadap hukum perkawinan di Indonesia. Kedua, perempuan tidak memiliki peran dalam proses penyusunan hukum keluarga, sehingga mereka menjadi minoritas dan sering ditempatkan dalam posisi stereotip. Ketiga, pembakuan peran dalam beberapa pasal UU No. 1 Tahun 1974 tentang Perkawinan dan KHI mendorong perempuan untuk memperjuangkan kesetaraan melalui reformasi hukum keluarga..]